First diagnosis of psychosis in the prison: results from a data-linkage study. Issue 6 (November 2019) - Chowdhury, Nabila Z.; Albalawi, Olayan; Wand, Handan; Adily, Armita; Kariminia, Azar; Allnutt, Stephen; Sara, Grant; Dean, Kimberlie; Lappin, Julia; O'Driscoll, Colman; Grant, Luke; Schofield, Peter W.; et al.
Abstract : Background: Psychosis is more prevalent among people in prison compared with the community. Early detection is important to optimise health and justice outcomes; for some, this may be the first time they have been clinically assessed. Aims: Determine factors associated with a first diagnosis of psychosis in prison and describe time to diagnosis from entry into prison. Method: This retrospective cohort study describes individuals identified for the first time with psychosis in New South Wales (NSW) prisons (2006–2012). Logistic regression was used to identify factors associated with a first diagnosis of psychosis. Cox regression was used to describe time to diagnosis from entry into prison. Results: Of the 38 489 diagnosed with psychosis for the first time, 1.7% ( n = 659) occurred in prison. Factors associated with an increased likelihood of being diagnosed in prison (versus community) were: male gender (odds ratio (OR) = 2.27, 95% CI 1.79–2.89), Aboriginality (OR = 1.81, 95% CI 1.49–2.19), older age (OR = 1.70, 95% CI 1.37–2.11 for 25–34 years and OR = 1.63, 95% CI 1.29–2.06 for 35–44 years) and disadvantaged socioeconomic area (OR = 4.41, 95% CI 3.42–5.69). Eight out of ten were diagnosed within 3 months of reception. Conclusions: Among those diagnosed with psychosis for the first time, only a small number were identified during incarceration with most identified in the first 3 months following imprisonment. This suggests good screening processes are in place in NSW prisons for detecting those with serious mental illness. It is important these individuals receive appropriate care in prison, have the opportunity to have matters reheard and possibly diverted into treatment, and are subsequently connected to community mental health services on release. Declaration of interest: None.